Endovascular Repair Using a 7-Branch Stent-Graft for a Thoracoabdominal Aortic Aneurysm With Variant Renovisceral Artery Anatomy. (April 2020) - Eleshra, Ahmed; Spanos, Konstantinos; Panuccio, Giuseppe; Gronert, Catharina; Rohlffs, Fiona; Kölbel, Tilo
Purpose: To present a case of endovascular repair using a custom-made 7-branch stent-graft for a thoracoabdominal aortic aneurysm (TAAA) in a patient with variations in the renovisceral artery anatomy.Case Report: A 70-year-old asymptomatic man presented with a 60-mm-diameter type IV TAAA. Due to severe coronary artery disease, an endovascular approach was elected. In the preoperative computed tomography angiography (CTA) scans, variations in the renovisceral artery anatomy included the common hepatic and splenic arteries deriving separately from the aorta and bilateral double renal arteries (RAs). A custom-made 7-branch stent-graft was manufactured to preserve all renovisceral arteries. The 7 branches were catheterized and connected with a steerable sheath from a femoral access. All branches were bridged to the target vessel (TV) with a self-expanding covered stent; 4 TVs also had balloon-expandable covered stents implanted. Final angiography and predischarge CTA showed patency of all 7 target vessels and corresponding visceral organs, with no endoleak. The patient was discharged on postoperative day 8 without complications. Six-month follow-up CTA demonstrated exclusion of the TAAA and patency of all 7 target vessels.Conclusion: Successful treatment of a TAAA in a patient with multiple variant renovisceral arteries was feasible with a custom-made 7-branch stent-graft, achieving a good early outcome.